Gender and Law Initiatives in Francophone Sub-Saharan Africa : Gender and Law Workshop in Francophone Sub-Saharan Africa (March 1998) - World Bank (Washington, DC, 2012)
As a result of two years of constructive dialogue between the World Bank (WB), government agencies and grassroots' associations involved in the advancement of women, a workshop for the Promotion of the societal status of women in Francophone Sub-Saharan Africa was organized in March 1998 in Cotonou by the Association of Women Jurists (AFJB) with WB technical and financial assistance. From the perspective of the Bank, this initiative provided a timely forum to discuss the potential of gender-responsive legal and judicial reforms as part of the overall WB poverty alleviation and economic growth strategy. These were to provide for: a) an exchange of views (between civil society and government agencies as well as between countries) on country-specific substance of law, law enforcement and legal literacy issues, as these relate to women's experience of discrimination; and b) a constructive comparison of the operational experiences of the participants in these areas of activity. As such, the workshop was understood to be the first step in a foreseen twelve month process leading to the development, formulation and financing of country-specific action plans, for the participant countries. These were very effectively structured and facilitated by the President and members of the AFJB. These included: eleven country-specific presentations discussed during the first day plenary and from this basis, the participants identified the three themes which provided the focus for the active working group debates on the second day: a) political leadership and the institutional and legal status of women; b) the weight of religion and traditions in socio-cultural discrimination against women; and c) women's access to resources in health, education, and financial services.